Carbonylmetallates—A Special Family of Nucleophiles in Aromatic and Vinylic Substitution Reactions. Issue 11 (25th January 2016) - Sazonov, Petr K.; Beletskaya, Irina P.
Abstract: Carbonylmetallates, [M(CO) n L] −, anionic transition‐metal carbonyl complexes, represent a large family of metal‐centered nucleophiles, and studying carbonylmetallates allows us to understand the differences in the behavior of the metal‐centered complexes versus heteroatom‐based nucleophiles. The mechanisms of carbonylmetallate reactions with aryl‐ and alkenyl halides have been examined by employing radical and, especially, carbanion trapping techniques. Carbonylmetallates show a marked preference for halogenophilic attack, and nucleophilic substitution with carbonylmetallates is often not a direct process, but proceeds through the initial attack at halogen with subsequent coupling of carbanion and HalM(CO) n L intermediates. Factors governing the competition between the halogenophilic and more common "carbophilic" reaction pathways, as well as the means of predicting the actual course of reaction are discussed. The review also considers other aspects of carbonylmetallate reactivity, including ion‐pairing effects, radical‐mediated nucleophilic substitution pathways, and the carbonylmetallate nucleophilicity scale in the reactions with π‐electrophiles. Abstract : Metal‐centered nucleophiles : Carbonylmetallates, [M(CO) n L] − show a marked preference for halogenophilic attack. Nucleophilic substitution with carbonylmetallates is often not a direct process, but proceeds through the initial attack at the halogen atom (see scheme). This review discusses factors governing the competition between the halogenophilic attack and attack at the carbon atom, as well as other aspects of carbonylmetallate reactivity.